2023
DOI: 10.1001/jamasurg.2023.1396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Specialist Palliative Care for Patients Undergoing Major Abdominal Surgery for Cancer

Abstract: ImportanceSpecialist palliative care benefits patients undergoing medical treatment of cancer; however, data are lacking on whether patients undergoing surgery for cancer similarly benefit from specialist palliative care.ObjectiveTo determine the effect of a specialist palliative care intervention on patients undergoing surgery for cure or durable control of cancer.Design, Setting, and ParticipantsThis was a single-center randomized clinical trial conducted from March 1, 2018, to October 28, 2021. Patients sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In Reply We appreciate the thoughtful response to our recently published trial . We agree that the null findings stem from studying a population with low unmet palliative care needs.…”
mentioning
confidence: 89%
“…In Reply We appreciate the thoughtful response to our recently published trial . We agree that the null findings stem from studying a population with low unmet palliative care needs.…”
mentioning
confidence: 89%
“…To the Editor Two important articles have been published in the JAMA Network in the last month regarding the early implementation of palliative care for patients undergoing surgery with a curative intent. Shinall et al investigated the effect of a palliative care intervention on physical and functional quality of life at 3 months, and Aslakson et al evaluated the effect of surgeon-palliative care co-management on patient-reported health-related quality of life at 3 months.…”
mentioning
confidence: 99%
“…Yet many questions remain unanswered when it comes to which populations would benefit from primary vs specialty palliative care services and who is best to provide those services. In this issue of JAMA Surgery , the study by Shinall et al identified a clear and distinct surgical population—namely, patients with resectable cancer undergoing major operations with curative intent. The trial was well designed and faithfully executed.…”
mentioning
confidence: 99%
“…Ultimately Shinall et al have given us pause to reconsider the role of routine perioperative-specialist palliative-care consultation in surgical oncology for curative intent. But rather than throwing the baby out with the bathwater, their work helps define important questions to be addressed by further investigations.…”
mentioning
confidence: 99%